Assessment of feedback for the teaching of nursing practice - Lorena de Godoi Montes; Cibele Isaac Saad Rodrigues; Gisele Regina de Azevedo
ABSTRACT Objective: Construct and validate instrument content for nursing consultation in an adult chemotherapy outpatient clinic. Method: Methodological study composed of two stages: elaboration of the instrument and validation of content. A literary review of the dimensions of customer care was carried out in the light of Theory of Basic Human Needs Theory, culminating in two instruments: one for admission consultation and other for follow-up. The content was validated by the evaluation of listed experts based on the adapted Fehring's Validation Model. Results: In the first round, two items of the admission instrument and three items of follow-up required reformulation. In the second round, there was an increase in agreement rate: 11% in the instrument of admission and 10% in follow-up. Final Consideration: The instrument represents a guideline for the Nursing Process and future research, but it cannot be seen as a substitute for nurses' knowledge and clinical reasoning.